Reporting trends of adverse effects from proton pump inhibitors to the food and drug administration. Issue 3 (5th May 2020) - Kruchko, David H.; Patel, Ami P.; Villines, Dana; Surjancev, Aleksandar; Ehrenpreis, Eli D.
Summary: Backgrounds & Aims: Recent publications have described new potential proton pump inhibitor (PPI)‐associated adverse effects (AEs). There is public interest and potential for lawsuits for these and other PPI‐related AEs. Post‐marketing surveillance reports of AEs can be found on the Food and Drug Administration Adverse Event Reporting System (FAERS) database. The aim of this study is to analyse reports of all PPI‐associated‐AEs to FAERS, focusing on reporter sources. Methods: A total of 9 144 290 FAERS reports from January 2012 to December 2018 were examined. Reporter sources analysed were lawyer, consumers and physicians. A reporter odds ratio (ROR) was used to determine the probability that one source was more likely to report AEs related to PPIs compared to others. Results: The number of reports for AEs from PPIs generally increased each year with all reporter sources. Reports for lawyers and physicians for renal disease both increased between 2015 and 2018. Physicians had an increase from 676 to 1112 cases of renal disease (64.5% increase), while lawyers had an increase of 4‐974 cases of renal disease (24 250% increase; ROR = 13.58; 95%; CI = 11.30‐16.33). Conclusion: The rapid increase in reports of PPI‐associated renal disease by lawyers suggests that lawyers are a potential source of interference on pharmacovigilance. RORs generated in this study demonstrate that the significant increase in renal‐related reporting of PPI adverse events to the FAERS is disproportionate for lawyer reporters.